Analisis Kemampuan Pemecahan Masalah Matematis Siswa Kelas Empat Sd 4 Dersalam Dalam Menyelesaikan Soal Cerita - Naisya Ramadhani; Putri Imatriyani Sholekhah; Ade Yolla Dliaul Aulia (Student Scientific Creativity Journal, 2023)
This study aims to describe students' mathematical problem solving skills in solving word problems. The population in this study were all fourth grade students at SD 4 Dersalam with a total sample of 24 students. The research method used is a qualitative approach with descriptive methods. The research instrument used was in the form of test questions (essays) and interview for mathematical problem-solving abilities in diagrammatic material. The data collection technique in this study has three stages of procedure namely; 1) preparation stage, 2) implementation stage, 3) final stage. Based on the results of the tests that have been given, the ability to solve mathematical problems in the good category is 14 students (58.3%), the medium category is 4 students (16.6%) and the low category is 6 students (25%). Based on the categories of mathematical problem solving abilities, namely good, sufficient and insufficient, it can be described as follows: 1. Students' Mathematical Problem Solving Ability in the Good Category 2. Students' Mathematical Problem Solving Ability in the Enough Category 3. Students' Mathematical Problem Solving Ability in the Poor Category.